2019
DOI: 10.3390/safety5030061
|View full text |Cite
|
Sign up to set email alerts
|

Coopetition as an Emerging Trend in Research: Perspectives for Safety & Security

Abstract: The study of coopetition has been evolving with rapid growth in the number of academic publications in this field. A number of literature reviews have been published focusing on nature, antecedents of coopetition and future perspectives of its implementation. Coopetition is proved to be beneficial for joint investments and Research and development (R&D) projects, and yet competitive games take place in the global markets that may lead to safety hazards. There are few studies that investigate possible persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 55 publications
1
35
0
1
Order By: Relevance
“…There are also a vast number of recent studies on the macroeconomic stability and its determinants Bilan, Rai sien_ e, et al, 2019;Bilan, Vasilyeva, Lyeonov, & Bagmet, 2019;Shvindina, 2019). This research confirmed and strengthened the conclusions that macroeconomic stability, as well as the trust crisis in the financial sector of the economy, is a multidimensional phenomenon, whose internal structure remains little known.…”
Section: Data Collection and Measure Of The Constructsupporting
confidence: 66%
“…There are also a vast number of recent studies on the macroeconomic stability and its determinants Bilan, Rai sien_ e, et al, 2019;Bilan, Vasilyeva, Lyeonov, & Bagmet, 2019;Shvindina, 2019). This research confirmed and strengthened the conclusions that macroeconomic stability, as well as the trust crisis in the financial sector of the economy, is a multidimensional phenomenon, whose internal structure remains little known.…”
Section: Data Collection and Measure Of The Constructsupporting
confidence: 66%
“…Among the research, areas are aimed at analyzing environmental indicators to build a balanced policy to ensure the safety of the country, particularly in ecology, energy, and food [28][29][30][31][32][33][34][35][36][37]. Researchers are studying the impact of population migration on the safety of countries [32] and the impact of migration in rural areas in terms of sustainable development [38][39][40][41][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…Бібліометричний аналіз у даній статті був проведений по аналогії з іншими статтями, зокрема [16][17][18][19][20].…”
Section: економіка глобалізаційні процеси в економіціunclassified